Letter from John R. Brinkley to William Jennings Lawson, Undated, KHS BrinkleyJ-to-LawsonW-undated - Carver, Ari (2025)
This document is a letter from Dr. John R. Brinkley to William Jennings Lawson. Dr. Brinkley was both a highly controversial and very successful medical figure in early 20th century. Known popularly as the "Goat-Gland Doctor," Brinkley built a multimillion-dollar empire based on the xenotransplantation of goat gonads into human patients to treat impotence and other ailments. He used radio extensively to promote himself and his practice. William Jennings Lawson the Texas Secretary of State from January 1941 until January 1943. He was appointed by Governor W. Lee O’Daniel, who served as governor of Texas from 1939 to 1941, when he ran in the special election for the United States Senate seat vacated by Morris Sheppard, who died in office on April 6, 1941.